2021
DOI: 10.1002/chem.202101275
|View full text |Cite
|
Sign up to set email alerts
|

NMR Crystallography Reveals Carbonate Induced Al‐Ordering in ZnAl Layered Double Hydroxide

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…5 ppm lower shift and different sign of the Haeberlen chemical shift anisotropy, D, than carbonate in the interlayer of both LDH and in sodium (bi)carbonate (Table S8, ESI †). This agrees with a recent study of ZnAl-LDH, which based on Rietveld refinement of PXRD data 19 obtained three possible monoclinic structures similar to 1M with one to three crystallographic inequivalent carbon sites, depending on the model and carbonate orientation. However, only a single 13 C resonance was observed experimentally for carbonate for the ZnAl-LDH investigated.…”
Section: Experimental Nmr Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…5 ppm lower shift and different sign of the Haeberlen chemical shift anisotropy, D, than carbonate in the interlayer of both LDH and in sodium (bi)carbonate (Table S8, ESI †). This agrees with a recent study of ZnAl-LDH, which based on Rietveld refinement of PXRD data 19 obtained three possible monoclinic structures similar to 1M with one to three crystallographic inequivalent carbon sites, depending on the model and carbonate orientation. However, only a single 13 C resonance was observed experimentally for carbonate for the ZnAl-LDH investigated.…”
Section: Experimental Nmr Resultssupporting
confidence: 92%
“…Recently, a combination of Rietveld refinement of PXRD data and multi-nuclear SSNMR also confirmed a lowering of the space group symmetry to monoclinic for ZnAl-LDH with carbonate in the interlayer. 19 Furthermore, both carbonate and bicarbonate (HCO 3 − ) have been identified in the interlayer of diamagnetic MgAl-LDH, where the high Al content (high cation layer charge) favours carbonate. 15 These two anions can be distinguished based on a 10 ppm difference in the 13 C isotropic chemical shift, δ iso ( 13 C), opposite signs of the 13 C chemical shift anisotropy and assignment based on a visual comparison with the 13 C MAS NMR spectra of sodium carbonate and bicarbonate in MgAl-LDH 15 and calcinated MgAl-LDH.…”
Section: Introductionmentioning
confidence: 99%
“…NMR has the unique ability to probe the coordination environment and dynamics of NMR active cations. By now it has become clear that the alkali cation affects all aspects of zeolite formation. , It impacts the distribution of aluminosilicate species in the solution and selects the most stable framework topology. With 23 Na, 39 K, and 133 Cs NMR, the degree of cations in the ion-paired state with oligomers versus hydrated cations in solution can be quantified (Figure ).…”
Section: In Situ Characterization Of Zeolite Crystallization In Hsil ...mentioning
confidence: 99%
“…Better understanding of the structure and degree of ordering would improve prediction of LDH properties. Theoretically, Me­(II) and Me­(III) in the hydroxide layers can be perfectly ordered at certain Me­(II)/Me­(III) ratios, for example, 2 and 3, but the actual arrangement has been reported to range from fully ordered to disordered or a mixture of the two (e.g., refs ). For example, a seminal study interpreted that order developed when Me­(II) and Me­(III) had comparable ion size but later work showed that order can also develop in unequally matched Me­(II/III) such as Mg­(II) and Al­(III) in hydrotalcite .…”
Section: Introductionmentioning
confidence: 99%